The general public as well as physiotherapists evaluate spinal flexion as dangerous regardless of their own low back pain history - Kavka, Tomas; Nedoma, Tomas; Blahova, Zuzana (Musculoskeletal science & practice, 2024)
BACKGROUND: Maladaptive fear of movement in individuals with low back pain may be associated with worse clinical outcomes. OBJECTIVE: To explore beliefs about the perceived dangers regarding different spinal postures within the Czech Republic. DESIGN: Exploratory cross-sectional study including physiotherapists and members of the general public. METHODS: Self-reported perceived safety/danger of "straight" and "flexed" spinal postures regarding 1) sitting, 2) lifting of light and 3) heavy object from the floor based on three pairs of photographs was measured using numeric rating scales (0-10, safe to dangerous) without any given context and in the context of low back pain. The sum of differences between the ratings of flexed and straight postures were used to calculate Bending Safety Beliefs Thermometer (BSBThermometer) total score potentially ranging -60‒60 (higher values indicates evaluation of flexed spinal postures as more dangerous in comparison to straight postures). RESULTS: 760 participants were included in the analysis. The mean BSBThermometer total score was 31.1 (SD 16.1) and higher scores were positively associated with being women (b = 14.8, 95% CI [9.9-19.8]); non-medical profession (b = 24.7, 95% CI [15.2-34.2]); age (b = 0.38, 95% CI [0.16-0.6]; and their interactions. There was no significant association with current low back pain status or history of low back pain. CONCLUSIONS: On average, participants evaluated "flexed" spinal postures as significantly more dangerous when compared with "straight" spinal postures, with only subgroups of physiotherapists scoring lower than the general public. Clinically, these beliefs could be targeted by individualized education, exposure-based interventions and public campaigns; however, further research is required.
Keywords: dospělí; Female; Adult; ženské pohlaví; průřezové studie; fyzioterapeuti; lidé; postura těla; Low Back Pain; Fear; strach; Cross-Sectional Studies; Male; Aged; Czech Republic; lumbalgie; Posture; Česká republika; lidé středního věku; senioři; mužské pohlaví; Physical Therapists; Middle Aged; Humans